Sociality and reproductive biology of the bushveld gerbil gerbilliscus leucogaster - Lotter, Tracy Kim (My University, 2013)
Unable to load abstract
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johanneburg, 2010.
Keywords: Gerbils.; Gerbils - Reproduction.; Gerbils - Socialization.